Financial incentives for antipsychotic depot medication: ethical issues - Claassen, Dirk (BMJ Group, 2007)
BACKGROUND: Giving money as a direct incentive for patients in exchange for depot medication has proved beneficial in some clinical cases in assertive outreach (AO). However, ethical concerns around this practice have been raised, and will be analysed in more detail here. METHOD: Ethical concern voiced in a survey of all AO teams in England were analysed regarding their content. These were grouped into categories. RESULTS: 53 of 70 team managers mentioned concerns, many of them serious and expressing a negative attitude towards giving money for depot adherence. Four broad categories of ethical concern following Christensen's concept were distinguished: valid consent and refusal (n = 5), psychiatric paternalism (n = 31), resource allocation (n = 4), organisational relationships (n = 2), with a residual category others and unspecified (n = 11). DISCUSSION: The main concerns identified are discussed on the background of existing ethical theories in healthcare and the specific problems of community mental health and AO. Points for practice are derived from this discussion. A way forward is outlined that includes informed consent and an operational policy in the use of incentives, further randomised controlled trials and qualitative studies, and continuing discussions with all stakeholders, especially service users.